Metamorphosis of the invasive ascidian Ciona savignyi: environmental variables and chemical exposure - Cahill, Patrick L.; Atalah, Javier; Selwood, Andrew I.; Kuhajek, Jeanne M. (PeerJ, 2016)
In this study, the effects of environmental variables on larval metamorphosis of the solitary ascidian Ciona savignyi were investigated in a laboratory setting. The progression of metamorphic changes were tracked under various temperature, photoperiod, substrate, larval density, and vessel size regimes. Metamorphosis was maximised at 18 °C, 12:12 h subdued light:dark, smooth polystyrene substrate, and 10 larvae mL−1 in a twelve-well tissue culture plate. Eliminating the air-water interface by filling culture vessels to capacity further increased the proportion of metamorphosed larvae; 87 ± 5% of larvae completed metamorphosis within 5 days compared to 45 ± 5% in control wells. The effects of the reference antifouling compounds polygodial, portimine, oroidin, chlorothalonil, and tolylfluanid on C. savignyi were subsequently determined, highlighting (1) the sensitivity of C. savignyi metamorphosis to chemical exposure and (2) the potential to use C. savignyi larvae to screen for bioactivity in an optimised laboratory setting. The compounds were bioactive in the low ng mL−1 to high µg mL−1 range. Polygodial was chosen for additional investigations, where it was shown that mean reductions in the proportions of larvae reaching stage E were highly repeatable both within (repeatability = 14 ± 9%) and between (intermediate precision = 17 ± 3%) independent experiments. An environmental extract had no effect on the larvae but exposing larvae to both the extract and polygodial reduced potency relative to polygodial alone. This change in potency stresses the need for caution when working with complex samples, as is routinely implemented when isolating natural compounds from their biological source. Overall, the outcomes of this study highlight the sensitivity of C. savignyi metamorphosis to environmental variations and chemical exposure.
Keywords: Ciona savignyi; Metamorphosis; Antifouling; Bioactivity; Environmental variables